2018
DOI: 10.1016/j.neuroimage.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect sizes of BOLD CVR, resting-state signal fluctuations and time delay measures for the assessment of hemodynamic impairment in carotid occlusion patients

Abstract: Background and purposeThe BOLD signal amplitude as a response to a hypercapnia stimulus is commonly used to assess cerebrovascular reserve. Despite recent advances, the implementation remains cumbersome and alternative ways to assess hemodynamic impairment are desirable. Resting-state BOLD signal fluctuations (rsBOLD) have been proposed however data on its sensitivity and dependence on baseline venous cerebral blood volume (vCBV) is limited. The primary aim of this study was to compare the effect sizes of rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Nevertheless, a limitation of this approach is that, if the subject’s spontaneous breathing pattern yields minimal fluctuations in their PETCO 2 level, there might not be enough signal variation for reliable CVR assessment. In fact, de Vis and colleagues showed that a hypercapnic stimulus of at least 2 mmHg above baseline PETCO 2 is necessary in order to evaluate any hemodynamic impairment ( De Vis et al, 2018 ). Another challenge is isolating low-frequency BOLD fluctuations arising from CVR mechanisms versus other physiologic noise sources or neural processes described above.…”
Section: Resting-state Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a limitation of this approach is that, if the subject’s spontaneous breathing pattern yields minimal fluctuations in their PETCO 2 level, there might not be enough signal variation for reliable CVR assessment. In fact, de Vis and colleagues showed that a hypercapnic stimulus of at least 2 mmHg above baseline PETCO 2 is necessary in order to evaluate any hemodynamic impairment ( De Vis et al, 2018 ). Another challenge is isolating low-frequency BOLD fluctuations arising from CVR mechanisms versus other physiologic noise sources or neural processes described above.…”
Section: Resting-state Methodsmentioning
confidence: 99%
“…While hypercapnia fMRI measures led to large effect sizes when detecting hemodynamic impairment, rs-fMRI ALFF/fALFF metrics only showed moderate effect sizes. Nevertheless, in both hypercapnia and resting-state CVR measures, resting CBV (using hyperoxia BOLD signal as a proxy) significantly explained a large portion of BOLD signal variance across the brain (hypercapnia: 53/37%; ALFF: 31/23%; fALFF: 29/14%, in healthy controls/patients, respectively) ( De Vis et al, 2018 ). Similar to ALFF, fALFF maps have also been employed as a voxelwise scaling factor of task-based fMRI analysis, significantly reducing inter-subject variability ( Kalcher et al, 2013 ).…”
Section: Resting-state Methodsmentioning
confidence: 99%
“…To date, most studies using a ramp protocol with SGD have been conducted specifically to test different physiological CVR relationships (i.e., linear, sigmoidal, etc.) (Bhogal et al, ) in order to better describe CVR (Bhogal et al, ; Sobczyk et al, ) or, simply, the utility in diagnosing steno‐occlusive diseases (De Vis et al, , ; Duffin et al, ). To our knowledge, no studies have specifically investigated, nor reported, the reproducibility of a ramp sequence to assess changes in CVR.…”
Section: Introductionmentioning
confidence: 99%
“…A ramping method with a relatively slow rate of change may be more tolerable for participants while maximizing the P et CO 2 range sampled. This may, potentially, uncover subtle pathophysiology by measuring the point at which a cerebral vessel or a brain region reach dilatory capacity (Bhogal et al, 2014;De Vis, Bhogal, Hendrikse, Petersen, & Siero, 2018;Duffin et al, 2017), which is not possible using a single step change.…”
mentioning
confidence: 99%
“…Conversely, other theories in the literature purport that rsfMRI BOLD fluctuations may reflect underlying changes in cerebrovascular integrity, that which itself may be further associated with increased independent risk for AD (Makedonov et al, 2013(Makedonov et al, , 2016Jahanian et al, 2014;DeVis et al, 2018). In such interpretations, a finding of a lack of regional variation in SD BOLD between participants with SCD and controls may reasonably reflect (i) a lack of significant difference in vascular anomalies between the two groups and/or (ii) dissociable relationships between SD BOLD and vascular factors within each group.…”
Section: Resting-state Sd Bold In Participants With Scd Compared To Amentioning
confidence: 95%